SAT0168 ONLY ONE THIRD OF REAL WORLD LUPUS PATIENTS MEET ELIGIBILITY CRITERIA FOR CLINICAL TRIALS: IMPLICATIONS FOR TRIAL VALIDITY AND GENERALISABILITY. (2nd June 2020) - Dyball, S.; Collinson, S.; Sutton, E.; Mccarthy, E.; Parker, B.; Bruce, I. N.
Abstract : Background: Despite unprecedented drug development in SLE, the paucity of approved therapies remains a significant challenge. Recent trials have highlighted the need for minimising heterogeneity within SLE populations; however, there is concern this results in the recruitment of patients that are not representative of the SLE population. Objectives: Our aim was to apply published trial eligibility criteria to patients with non-renal SLE in a large UK-wide register to quantify how accurately these clinical trials represent a real-world cohort. Methods: A literature review of all major published double-blinded randomised phase III trials in non-renal SLE was performed (n=12). Inclusion and exclusion criteria common across the majority of clinical trials were applied to all patients recruited to the BILAG-BR (BILAG biologics register) starting either biological therapy or standard of care (SOC). We applied available data to common inclusion criteria including age ≥18 years, ACR 1997 SLE classification criteria, positive anti-dsDNA or ANA antibodies, active disease (defined as a BILAG A in 1 domain or a BILAG B in ≥2 domains, or a SLEDAI ≥6); and common exclusion criteria including restricted medication rules, active renal or neurological SLE (defined as a BILAG A in either domain), a history of hepatitis B or C, a history of malignancy (excluding basal cell carcinoma), CKD stage 4 or 5, a UPCR ≥100mg/mmol, and cytopenias (defined as neutrophils <1.0 x10 9 /L, platelets <10 x10 9 /L or Hb <70g/L). Baseline variables were compared using chi-squared test. Results: As of July 2018, 837 patients were recruited to the BILAG-BR starting either SOC (n=125) or a biologic therapy (n=712). The commonest biologic and SOC therapy was rituximab (n=662, 93%) and mycophenolate (n=64, 51%) respectively. Patients taking SOC were more likely to have inactive disease, as well as having higher steroid doses and less exposure to previous cyclophosphamide or B cell therapy. In the biologic and SOC groups, 476 (67%) and 71 (57%) respectively met all inclusion criteria (table 1 ). One or more exclusion criteria were met by 324 (46%) of the biologics group and 46 (37%) of the SOC group. As such, 562 (67%) patients were not eligible to enrol in a clinical trial. The patients not eligible to participate were similar in age (P=1.0), gender (P=0.7) and ethnicity (p=0.5) to those who were eligible. Median disease duration was longer in patients eligible to participate (2.9 vs. 5.1 years, p<0.01). Conclusion: In a large national register of SLE patients, we found that two thirds of patients would not be eligible for recruitment to clinical trials using published inclusion and exclusion criteria. These results suggest that clinical trial recruits are not fully representative of the target disease population. This limits the generalisability of clinical trial results and supports the need for evidence from real world studies to fully understand the effectiveness of new therapies. Disclosure of Interests: Sarah Dyball: None declared, Sophie Collinson: None declared, Emily Sutton: None declared, Eoghan McCarthy: None declared, Ben Parker Grant/research support from: GSK and Sanofi Genzyme, Consultant of: GSK, AstraZenaca, UCV, Abbvie, Pfizer, BMS, Celltrion, Ian N. Bruce Grant/research support from: Genzyme Sanofi, GSK, and UCB, Consultant of: Eli Lilly, AstraZeneca, UCB, Iltoo, and Merck Serono, Speakers bureau: UCB